Autonomous Agents and Multi-Agent Systems - Sierra, Carles; Luck, Michael; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The journal provides a leading forum for disseminating significant original research results in the foundations, theory, development, analysis, and applications of autonomous agents and multi-agent systems. Specific topics of interest include, but are not restricted to: Agent decision-making architectures and their evaluation, including deliberative, practical reasoning, reactive/behavioural, plan-based, and hybrid architectures. Cooperation and teamwork, including organizational structuring and design for multi-agent systems, self-organization, emergent functionality and swarm intelligence. Multi-agent planning and planning for multi-agent systems, and the coordination of multi-agent plans and activities. Computational auction systems, computational market systems, algorithmic/automated mechanism design, automated negotiation, computational aspects of game theory (cooperative and non-cooperative), and computational social choice theory. Knowledge representation and reasoning for, and logical foundations of, autonomous agents and multi-agent systems. Agent programming languages - their implementation, semantics, and evaluation. Distributed constraint processing and distributed constraint optimization. Multi-agent argumentation and dialogue, conflict detection and resolution. Multi-agent learning, co-learning, and evolutionary approaches in multi-agent systems. Learning agents, including: computational architectures for learning agents; evolution, adaptation; multi-agent learning. Agent communication languages, their semantics, pragmatics, and implementation, and agent communication protocols and conversations. Conventions, commitments, norms, obligations, and social laws in multi-agent systems, and models of trust and reputation. Believable and synthetic agents and characters, and human-agent interaction. Environments, testbeds, and programming languages for experimentation with, and analysis of, agent systems. Ontologies for agent systems, agents and the semantic web, agents and semantic web services, Grid-based systems, and service-oriented computing. Robotic agents, including: integrated perception, cognition, and action; cognitive robotics; robot planning (including action and motion planning); multi-robot systems. Agents as a software engineering paradigm, including agent system development, specification and verification of agent systems, methodologies for autonomous agents and multi-agent systems, analysis and design for multi-agent systems, evaluations of different approaches to developing agent systems, and significant practical experiences with agent system. Exploration of relationships between agents and other disciplines such as psychology, linguistics, philosophy, and human-computer interaction; and the relationship between multi-agent systems and other disciplines such as economics/game theory, sociology, and organization theory. Significant, novel applications of agent technology. Comprehensive reviews and authoritative tutorials of research and practice in agent systems. Comprehensive and authoritative reviews of books dealing with agents and multi-agent systems.
Keywords: Computer organization; Software engineering; User interfaces (Computer systems).; Artificial Intelligence; Computer Systems Organization and Communication Networks; Artificial Intelligence; Software Engineering/Programming and Operating Systems; User Interfaces and Human Computer Interaction